Optimization of Antibacterial Metabolite Production and Antioxidant Activity of Endophytic Fungi Isolate from Kelakai (Stenochlaena palustris) - Muthma'innah Mashar, Harlyanti; Supriyono, Teguh; Suhaera, Suhaera; Ismail, Ismail; Dali, Dali; Isrul, Muhammad (Formosa Journal of Science and Technology, 2023)
This research aims to optimize the production of antibacterial metabolites and test the antioxidant activity of endophytic isolates from kelakai (Stenochlaena palustris). The research results showed that the optimum growth profile of the isolate showed that exponential growth only started on day 1 and reached a maximum on day 17. Based on pH variations, it shows that pH 7 is the optimum pH in inhibiting bacterial growth, and based on variations in carbon sources, it shows that fructose is a better carbon source than glucose. Antimicrobial activity test using ethyl acetate extract from endophytic fungal fermentate based on differences in pH and carbon source showed antimicrobial activity against S. aureus and E. coli with the inhibition zone diameters being 13.50 mm and 11.35 mm, respectively.